Spatial Thinking With Comics in Geography Education - von Reumont, Frederik; Budke, Alexandra (Frontiers in Education, 2021)
Spatial thinking is a key asset in Geography education. Thus pre-service Geography teachers need to be trained in spatial thinking. Since comics seem to be a good approach to teaching Geography, in our study we wanted to find out about the possibilities to teach spatial thinking with comics. How do students put their spatial thinking into practice while producing their own comics? What does this mean for the learning process? We analyzed comics, which were produced by teacher students in a mid-level university seminar for the use in the geography classroom. In the analysis of the comics produced by our students we gauged their abilities to think spatially in terms of the spatial concepts developed by Wardenga (2002). We contextualized the visual output of the comics with a survey we conducted among the participants, which we analyzed using qualitative content analysis. We found that our students had difficulties assessing the potential of comics to teach spatial thinking in a purely verbal and theoretical way. However, in their own productions they showed high levels of creativity expressing spatial concepts. Comics produced by learners offer unique opportunities for the reflection and assessment of their ways of spatial thinking.